Technical Efficiency of Small-Scale Pig Farming in Indonesia - Keraru, Ester Nurani; Harianto, Harianto; Yusalina, Yusalina (SOCA: Jurnal Sosial Ekonomi Pertanian, 2023)
Live pigs are still the mainstay of livestock sub-sector exports in Indonesia. Although pig farming in Indonesia has competitiveness in the international market, its productivity shows a declining condition. The purpose of this research is to measure the level of technical efficiency of small-scale pig breeding and fattening businesses. The data used come from the results of the Farm Household Survey conducted by the Central Bureau of Statistics (BPS). The survey was conducted in 20 provinces in Indonesia, with a sample size of 6,681 small-scale or household-scale pig farming. The research used the Stochastic Production Frontier (SPF) model to measure the level of technical efficiency of pig farming and used the maximum likelihood method to estimate it. The results showed that the level of technical efficiency of pig farming is relatively low. The average technical efficiency level of fattening pig farming is higher than that of the breeding. The factors of farming experience, market orientation, and feed type combination have a positive influence in improving efficiency. Public policies that improve pig farmers' access to farm inputs and markets are expected to significantly improve the productivity of small-scale pig farming.